Examining the effect of antibiotic administration timing on infection rates following hernia surgery - Tadayon, Niki; Mirhosseini, Mohammadmoein (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: Hernia is the weakening or disruption of the fibrous-muscle tissue of the body wall through, which intra-abdominal structures pass. The lack of consensus about the antibiotic prescription and the appropriate time led to some non-appropriate antibiotic use. Recognition of the best time can help to better preventive approaches in the patients. Materials and Methods: In this study, 110 male patients who were electively referred for inguinal hernia repair were enrolled and divided into two sections of 55 patients, with one group receiving preoperative antibiotics and the other receiving postoperative antibiotics. The infection rates were compared between the groups. Results: The results of this study showed that age, BMI, duration of operation, and hospital stay were alike across the groups (P > 0.05). There was no infection in any of the classes. Conclusion: Overall, the findings of this study indicate that the rate of infection in cases of mesh reconstruction of inguinal hernia is minimal, and the rate is the same in those with a preoperative and postoperative antibiotic prescription. This suggests the guidelines should be changed in order to shorten the duration and dosage of antibiotic treatment as well as the length of stay for these patients in hospitals.